Analisis Sentimen Ulasan Pengguna Aplikasi Game Sky Childern Of The Light Menggunakan Metode Algoritma Naive Bayes (Studi Kasus Tingkat Kepuasan Pengguna) - Hafidz Syauqie; Augie Sugiarto Nunka; Mu. Aldi Rahmad Fahrozi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This research use the Naive Bayes algorithm to classification of user reviews of the Sky Childern Of The Light application from the Google Play Store. The Sky Childern Of The Light application is a popular online game, because it offers a unique and immersive playing experience. This method was chosen because of its simplicity, speed, ease of interpretation, and suitability for high-dimensional data. The advantages of Naive Bayes are the accuracy and efficiency of calculations, fast results and presentation. The data collected was 1500 data with a classification ratio of 8:2 with an accuracy value of 87% using the Naïve Bayes algorithm. This method is very good at analyzing the sentiment of the Sky Children Of The Light application.